Managerial Competence of Principals and Its Impact on Teacher Work Motivation in Elementary Schools of Aceh Tamiang - Khadijah, Khadijah; Marwan, Marwan; Khairani, Cut (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
Teacher motivation is a significant barrier for improving educational quality, especially in rural and resource-limited institutions. This study examines the impact of principals' managerial competence—executed through the functions of planning, organizing, actuating, and controlling (POAC)—on improving teacher work motivation in elementary schools. Data were gathered using a qualitative methodology through in-depth interviews, observations, and recording at five public elementary schools in Gugus III Ceding Ayu, Aceh Tamiang, Indonesia. The results indicate that adaptive managerial methods, defined by participatory planning, supportive supervision, transparent communication, and context-sensitive leadership, substantially enhance teachers' enthusiasm, commitment, consistency, and teamwork. Nonetheless, challenges persist about the uniformity of follow-up oversight and the fair allocation of responsibilities. This study theoretically extends the contextual application of the POAC framework in rural educational environments and practically provides a robust model of adaptive school management to enhance teacher involvement in underprivileged areas.